Transformation of collective agricultural productive in East Germany and its lessons to North Korea - Axel Wolz (2004)
This paper aims to summarize the main steps and experiences of the agricultural transformation process in Germany since 1989 when the Eastern part of the country embarked on a transition from a socialist central-planning economy to a market economic system. At some stages it is referred to the transformation process of other countries, in general of Central and Eastern Europe (CEEC). The paper will outline the major steps and consequences of agricultural transformation. A gradual approach of agricultural transformation and adjustment to a market economic system should be adopted and a big bang avoided for North Korea. In a market economy system the government has to give up any role to guide and manage the economy including the agricultural sector. However, it has to provide a sound legal framework which ensures the rights and obligations of private individuals and companies in a fair manner. In addition, while the state is converting the economy from a planning to a market economic system, it has to support the people to get used to this new system over a transitional period.
Keywords: East Germany; North Korea; Agricultural transformation; Central-planning economy; Market economy; East Germany; North Korea; Agricultural transformation; Central-planning economy; Market economy